Integrative Analysis of Small RNA and mRNA Expression Profiles Identifies Signatures Associated With Chronic Epididymitis - Gong, Jialei; Wang, Peng; Liu, Jin-Chuan; Li, Jianlin; Zeng, Qun-Xiong; Yang, Chen; Li, Yanfeng; Yu, Di; Cao, Dandan; Duan, Yong-Gang (Frontiers in Immunology, 2022)
Chronic epididymitis (CE) refers to a long-lasting inflammatory condition of the epididymis, which is considered the most common site of intrascrotal inflammation and an important aetiological factor of male infertility. Recent studies demonstrate that small RNAs secreted from epididymal epithelium modulate embryo development and offspring phenotypes via sperm transmission, and the resulting modifications may lead to transgenerational inheritance. However, to date, the genome-wide analysis of small RNA together with the transcriptomic expression profiles of human epididymis and CE is still lacking. In this study, we facilitated next-generation sequencing and bioinformatics to comprehensively analyze the small RNA and mRNA in an integrative way and identified signatures associated with CE. Both of the small RNA and mRNA expression data demonstrated relatively larger molecular differences among the segmental region of the epididymides, including caput, corpus, and cauda, than that of the inflammatory conditions. By comparing the inflamed caputs to the controls, a total of 1727 genes (1220 upregulated and 507 downregulated; 42 most significant genes, adjusted P <0.05) and 34 miRNAs (23 upregulated and 11 downregulated) were identified as differentially expressed. In silico functional enrichment analysis showed their roles in regulating different biological activities, including leukocyte chemotaxis, extracellular milieu reconstruction, ion channel and transporter-related processes, and nervous system development. Integrative analysis of miRNA and mRNA identified a regulatory network consisting of 22 miRNAs and 31 genes (miRNA-mRNA) which are strong candidates for CE. In addition, analysis about other species of small RNA, including (miRNA), piwi-interacting RNA (piRNA), tRNA-derived small RNA (tsRNA), Y RNA, and rsRNA identified the distinct expression pattern of tsRNA in CE. In summary, our study performed small RNA and miRNA profiling and integrative analysis in human CE. The findings will help to understand the role of miRNA-mRNA in the pathogenesis of CE and provide molecular candidates for the development of potential biomarkers for human CE.